Trends in Cardiovascular Disease–Related Mortality in Texas - Muhammad Shariq Usman, MD; Adeena Jamil, MBBS; Zainali Chunawala, MD; Mahboob Alam, MD; Vijay Nambi, MD, PhD; Layla A. Abushamat, MD, MPH; Arunima Misra, MD; Salim S. Virani, MD, PhD; Christie M. Ballantyne, MD; George E. Taffet, MD; Khurram Nasir, MD; Sachin Goel, MD; et al. (Texas Heart Institute Journal)
Background: Cardiovascular disease (CVD) is associated with high mortality in the United States, but the burden of CVD mortality is unevenly distributed between demographic and geographic subgroups, with poor characterization of state-specific trends. In this study, the disparities in CVD-related mortality trends in Texas and the United States from 1999 to 2019 were assessed. Methods: Trends in CVD-related mortality were evaluated through analysis of the Multiple Causes of Death Files from the National Center for Health Statistics. Crude and age-adjusted mortality rates (AAMRs) per 100,000 population with associated annual percentage changes were determined. Joinpoint regression was used to assess trends in the CVD-related mortality rates. Results: Between 1999 and 2019, 29,455,193 CVD-related deaths were reported in the United States, of which 1,937,166 occurred in Texas. After an initial decline in the overall AAMR in Texas (annual percentage change, −2.5 [95% CI, −2.8 to −2.1]), a steady level was maintained from 2009 to 2019 (annual percentage change, 0.2 [95% CI, −0.5 to 0.2]). In the United States, after initial decline, AAMR plateaued from 2011 to 2019. Overall, CVD-related AAMR was slightly higher in Texas than in the overall United States (AAMR, 674.1 [95% CI, 673.2-675.1] vs 654 [95% CI, 653.8-654.3]). Men, non-Hispanic Black people, and people 85 years of age and older had the highest AAMRs in Texas and nationwide. Nonmetropolitan areas, both nationally and in Texas, consistently had higher mortality rates. The AAMRs also varied significantly by county within Texas. Conclusion: Despite an initial period of decline, CVD-related mortality rates have plateaued in Texas and the United States. Higher AAMRs were observed in Texas than in the overall United States. Prevalent disparities also exist based on demographic and geographic subgroups.